Purchase intention toward organic food among young consumers using theory of planned behavior: role of environmental concerns and environmental awareness - Ahmed, Naveed; Li, Cai; Khan, Asadullah; Qalati, Sikandar Ali; Naz, Shumaila; Rana, Faisal (Journal of environmental planning and management, 2021)
This study aims to propose an extended model of the theory of planned behavior (TPB) which helps us to investigate young Chinese consumers from college and university, and who are aged 18 to 30 years, on purchase intention for organic food. Using a sample of 515, analyses were done using structural equation modeling. The findings indicated that attitude (A), subjective norms (SNs), and perceived behavioral control (PBC) have positive effects on the purchase intention of young consumers for organic food. Moreover, attitude has a positive effect on environmental concerns (EC). Furthermore, EC has a positive effect on young consumers' purchase intentions for organic food. Findings indicated that EC positively mediates the association between attitude and young consumers' purchase intentions for organic food. More importantly, the relationship between all latent variables (A, SNs, PBC) and purchase intention by young consumers is positively moderated by environmental awareness.